Antigenic and physicochemical characterization of Hepatitis B surface protein under extreme temperature and pH conditions. Issue 43 (8th October 2019) - Lopes, J.L.S.; Oliveira, D.C.A.; Utescher, C.L.A.; Quintilio, W.; Tenório, E.C.N.; Oliveira, C.L.P.; Fantini, M.C.A.; Rasmussen, M.K.; Bordallo, H.N.; Sant'Anna, O.A.; Botosso, V.F.
Highlights: HBsAg is an α/β protein quite stable to pH treatment (from 5.5 to 8.5). Temperatures higher than 45 °C might promote some level of HBsAg unfolding. Fully HBsAg denaturation with loss of its antigenicity properties occurs at 100 °C. HBsAg vaccine stability is preserved even after 6 months storage. Abstract: Hepatitis B virus causes acute and chronic infections in millions of people worldwide and, since 1982, a vaccine with 95% effectiveness has been available for immunization. The main component of the recombinant hepatitis B vaccine is the surface antigen protein (HBsAg). In this work, the effect of pH, ionic strength and temperature on the native state of the HBsAg antigen were studied by a combination of biophysical methods that included small angle X-ray scattering, synchrotron radiation circular dichroism, fluorescence and surface plasmon resonance spectroscopies, as well as in vivo and in vitro potency assays. The native conformation, morphology, radius of gyration, and antigenic properties of the HBsAg antigen demonstrate high stability to pH treatment, especially in the pH range employed in all stages of HBsAg vaccine production and storage. The HBsAg protein presents thermal melting point close to 56 °C, reaching a more unfolded state after crossing this point, but it only experiences loss of vaccine potency and antigenic properties at 100 °C. Interestingly, a 6-month storage period does not affect vaccine stability, and the results are similar when the protein is kept under refrigerated conditions or at room temperature (20 °C). At frozen temperatures, large aggregates (>200 nm) are formed and possibly cause loss of HBsAg content, but that does not affect the in vivo assay. Furthermore, HBsAg has a well-ordered secondary structure content that is not affected when the protein is formulated with silica SBA-15, targeting the oral delivery of the vaccine. The combined results from all the characterization techniques employed in this study showed the high stability of the antigen at different storage temperature and extreme values of pH. These findings are important for considering the delivery of HBsAg to the immune system via an oral vaccine.